2013
DOI: 10.1016/j.jbiomech.2013.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Returning to overuse activity following a supraspinatus and infraspinatus tear leads to joint damage in a rat model

Abstract: Large rotator cuff tears (supraspinatus and infraspinatus) are common in patients that perform overhead activities (laborers, athletes). In addition, following large cuff tears, these patients commonly attempt to return to pre-injury activity levels. However, there is a limited understanding of the damaging effects on the uninjured joint tissues when doing so. Therefore, the objective of this study was to investigate the effect of returning to overuse activity following a supraspinatus and infraspinatus tear o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 32 publications
1
18
0
1
Order By: Relevance
“…Specifically, the group without biceps tenotomy had a more laterally directed force, a decreased propulsion force, and an increased braking force. These changes have also been shown to occur after shoulder injury in this animal model system [17,18] and may be indicative of an altered loading environment that could be present in the human condition. However, this finding disagrees with previous studies.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Specifically, the group without biceps tenotomy had a more laterally directed force, a decreased propulsion force, and an increased braking force. These changes have also been shown to occur after shoulder injury in this animal model system [17,18] and may be indicative of an altered loading environment that could be present in the human condition. However, this finding disagrees with previous studies.…”
Section: Discussionmentioning
confidence: 67%
“…In addition, cartilage histology (modified Mankin score and cell density) was not significantly different between groups for any of the regions. Previous studies have identified cartilage damage in the presence of cuff tears [16][17][18], and therefore, performing long head of the biceps tenodesis or tenotomy has been a concern among surgeons [4]. However, no long-term followup studies exist evaluating whether patients are at a higher risk for glenohumeral arthritis after long head of the biceps tenodesis or tenotomy.…”
Section: Figmentioning
confidence: 99%
“…50 Alternatively, a combination of overuse followed by acute injury has also been used to model rotator cuff tendinopathy. 51,52 Use of these paradigms has led to the conclusion that damage to rotator cuff tendons leads to an increase in atrophy and/or fatty infiltration of the muscle. 46-48 It has also been discovered that acute rupture of the tendon leads to decreased regulation of the signaling pathway that maintains muscle mass in response to mechanical loading (Akt/mTOR), but denervation without transection of the tendon leads to upregulation in this pathway.…”
Section: Rotator Cuffmentioning
confidence: 99%
“…Current research has not clearly elucidated the role of mechanical loading in the pathological shoulder joint, but also the benefits/drawbacks of post-operative immobilisation continue to be confounding. 5 Methods such as casting immobilisation, 49,55 botulinum toxin injections, 56,57 and overuse activity 51,52 have been used to alter the mechanical loads imparted upon the shoulder joint before and after surgical intervention. Results suggest that pre-operative immobilisation may have beneficial effects on long-term healing because this approach has resulted in improved cellularity and collagen organisation, while simultaneously increasing the Collagen I:Collagen III ratio, which is indicative of the end stages of tendon healing.…”
Section: Rotator Cuffmentioning
confidence: 99%
“…If a rotator cuff tear is present, this can cause force imbalances, which have negative implications for the surrounding tissues if left untreated (Peltz et al, 2009; Perry et al, 2009; Reuther et al, 2013b). While past studies have determined the mechanical mechanisms by which rotator cuff tears lead to further joint damage (Reuther et al, 2014, 2013a, 2013b; Thomas et al, 2014), the implications of associated surgical procedures, such as full detachment of the long head of the biceps (LHB) via tenotomy, have yet to be fully examined.…”
Section: Introductionmentioning
confidence: 99%